PERLINDUNGAN HUKUM BAGI PEMENANG LELANG ATAS GUGATAN PEMBATALAN LELANG OLEH DEBITOR ATAU PEMILIK JAMINAN - Mantara, Marselia Yolanda (JURNAL MINUTA, 2019)
The granting of a credit by a bank is usually followed by collateral that’s given by the debtor. The debtor does not only borrow funds from the bank but also gives collateral of equal or greater value to the bank.The function of collateral is to assure the creditor that that the debtor’s debt can be paid off. In practice, when a credit loan becomes bogged down, the bank can execute collateral given by the debtor through a process where the debtor must be declared unable to pay his debt to the creditor.One solution to this problem is via auctioning. An auction is a public sale of goods preceded by an Auction Announcement where the price is offered verbally or in writing. Its price will increase or decrease until the highest bid is found.